1998
DOI: 10.1091/mbc.9.7.1891
|View full text |Cite
|
Sign up to set email alerts
|

RhoA GTPase and Serum Response Factor Control Selectively the Expression of MyoD without Affecting Myf5 in Mouse Myoblasts

Abstract: MyoD and Myf5 belong to the family of basic helix-loop-helix transcription factors that are key operators in skeletal muscle differentiation. MyoD and Myf5 genes are selectively activated during development in a time and region-specific manner and in response to different stimuli. However, molecules that specifically regulate the expression of these two genes and the pathways involved remain to be determined. We have recently shown that the serum response factor (SRF), a transcription factor involved in activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
122
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(136 citation statements)
references
References 59 publications
11
122
3
Order By: Relevance
“…Here, we present the first evidence that the nuclear localization of Myf5 is negatively controlled by RhoG/Rac1 and Cdc42Hs, likely through the activation of the JNK pathway. In contrast to MyoD, the myogenic factor Myf5 is not regulated by the RhoA/SRF pathway in C2C12 cells (Carnac et al, 1998), in agreement with our own results with L6 cells. Furthermore, expression of the DN Rac1 and Cdc42Hs mutants does not affect Myf5 localization, suggesting that DN and active Rac1 and Cdc42Hs mutants inhibit myogenesis through distinct signaling pathways.…”
Section: Opposing Roles For Rhog/rac1/cdc42hs and Rhoa In Regulating supporting
confidence: 93%
See 2 more Smart Citations
“…Here, we present the first evidence that the nuclear localization of Myf5 is negatively controlled by RhoG/Rac1 and Cdc42Hs, likely through the activation of the JNK pathway. In contrast to MyoD, the myogenic factor Myf5 is not regulated by the RhoA/SRF pathway in C2C12 cells (Carnac et al, 1998), in agreement with our own results with L6 cells. Furthermore, expression of the DN Rac1 and Cdc42Hs mutants does not affect Myf5 localization, suggesting that DN and active Rac1 and Cdc42Hs mutants inhibit myogenesis through distinct signaling pathways.…”
Section: Opposing Roles For Rhog/rac1/cdc42hs and Rhoa In Regulating supporting
confidence: 93%
“…We found that expression of activated RhoA potentiates early steps of myogenesis, because it increases the expression of myogenin, troponin T, and MHC. These data are in agreement with recent studies showing that RhoA but not Rac1/Cdc42 signaling is an integral part of the skeletal muscle differentiation pathway (Carnac et al, 1998;Wei et al, 1998). Nevertheless, expression of activated RhoG, Rac1, and Cdc42Hs fully inhibits myogenesis of rat L6 myoblasts, preventing the expression of myogenin, troponin T, and MHC.…”
Section: Opposing Roles For Rhog/rac1/cdc42hs and Rhoa In Regulating supporting
confidence: 93%
See 1 more Smart Citation
“…4A). Assays using different mutants of RhoA confirmed our conclusion: p120-catenin interacted better with the RhoA Thr19Asn mutant, an inactive RhoA mutant (4,32), than with the RhoA Gln63Leu mutant, a RhoA mutant with impaired GTPase activity and, therefore, constitutively bound to GTP molecules (15) (Fig. 4B, lanes 3 and 4).…”
supporting
confidence: 77%
“…RhoA is an integral part of the skeletal muscle differentiation pathway and plays an obligatory role during myogenic induction (Carnac et al, 1998;Wei et al, 1998;Meriane et al, 2000). In addition, the level of RhoA GTP is increased by a pathway that promotes the commitment to myogenesis (Charrasse et al, 2003).…”
Section: Rhoa Gtpase Activity Decreases At the Onset Of Myoblast Fusionmentioning
confidence: 99%